Improvement of hydrothermal response of corn seed under drought stress using abscisic acid, gibberellic acid, and salysilic acid - Elham Bahrabadi; R. Tavakkol Afshari; Mehdi Nassiri Mahallati (علوم و فناوری بذر ایران, 2022)
In order to evaluate the effect of temperature, drought and priming on the percentage and rate germination of corn seeds, a factorial experiment based on a completely randomized design with four replicates was conducted. Treatments included eight temperature (5, 10, 15, 20, 25, 30, 35, 40 and 45 ºC), four drought potential (0, -0.4, -0.8 and -1.2 MPa), and five priming (control, hydroprimin, GA priming, ABA priming and, SA ptiming). Both percentage and rate of germination were inhibited at osmotic potentials ≤−0.8 MPa PEG. At 35 ºC temperature. Germination percentage of unprimed seeds was reduced from 94 to 36% in −1.2 MPa. Under these conditions, gibberellic acid hormone treatment improved seed germination. The effect of temperature on germination can be defined in terms of cardinal temperatures. We compared three non-linear regression models (Dent-like, segmented and beta). The outcome revealed that the Dent-like function was suitable for use in describing seed germination response to temperature. The base, optimum 1, optimum 2 and ceiling temperature were estimated to be 9.51, 24.12, 35 and 44.62 °C, respectively. The response of germination rate to both temperature and water potential can be described as a non-linear function of the hydrothermal model. According to the results of this study, hydropriming, gibberellic acid, and salicylic acid increased the mean deviation of the base temperature compared to non-priming treatment, increasing the standard deviation of the base temperature indicates the ability of seed germination in different osmotic potentials.